La administración pública ante los derechos de los particulares - Fernández Ruiz, Jorge (2015)
Legal rules regulate external human behavior coercively. Without these rules, both State and society are unconceivable, although the State is, in turn, essential for the operation of legal rules, that is, of Law. Put in another way, State and Law essentially and mutually require each other. However, legal rules cannot encompass every external human behavior because it must respect a minimum scope of unrestricted freedom of human beings, which are considered as an entity within its own purpose. The inextinguishable and inalienable minimum scope of human freedom represents its subjective rights, known as fundamental rights.